Motion Capture Depends Upon the Common Fate Factor Among Elements. (December 2017) - Ichikawa, Makoto; Masakura, Yuko
When observers move the head backwards and forwards while fixating on the center of the concentric circles that consist of oblique lines, they see illusory rotation of those circles. If several dots are superimposed on the proximity to the inner concentric circles, observers see the illusory rotation not only for the circles but also for the superimposed dots. This illusory rotation of the dots is based on motion capture. In this study, in order to understand the basis of the motion capture, we examined how motion signal with different directions (rotation, expansion/contraction, and horizontal translation) in terms of motion on a display, as well as illusory motion signal from the oblique components, affects the motion capture. If the stimulus presented rotation with expansion/contraction, or rotation with horizontal translation for the entire stimulus, then observers tended to perceive motion capture for the superimposed dots. However, if the stimulus presented only rotation of the circles, then observers tended to perceive induced motion for the superimposed dots. These results suggest that the existences of the common fate factor for the entire stimulus determine the means of allocating and integrating the motion signal in each element in the stimulus to generate motion capture.